2021
DOI: 10.1038/s41598-021-82300-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying lumbar vertebral perfusion by a Tofts model on DCE-MRI using segmental versus aortic arterial input function

Abstract: The purpose of this study was to investigate the influence of arterial input function (AIF) selection on the quantification of vertebral perfusion using axial dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI). In this study, axial DCE-MRI was performed on 2 vertebrae in each of eight healthy volunteers (mean age, 36.9 years; 5 men) using a 1.5-T scanner. The pharmacokinetic parameters Ktrans, ve, and vp, derived using a Tofts model on axial DCE-MRI of the lumbar vertebrae, were evaluated using var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…In this study, we demonstrated that manual phase-shift delays of the AIF signal intensity curve in cases of spinal metastases whose standard analysis yielded suboptimal perfusion results can increase the diagnostic accuracy of perfusion parameters. These findings are concordant with the results of Liu et al, whose controlled simulations showed that Vp increases as AIF delay time increases in healthy individuals [16].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, we demonstrated that manual phase-shift delays of the AIF signal intensity curve in cases of spinal metastases whose standard analysis yielded suboptimal perfusion results can increase the diagnostic accuracy of perfusion parameters. These findings are concordant with the results of Liu et al, whose controlled simulations showed that Vp increases as AIF delay time increases in healthy individuals [16].…”
Section: Discussionsupporting
confidence: 93%
“…Ideally, AIF should be sampled at the vascular inlet of the target tissue. Liu et al suggested using spine segmental arteries for V p analyses instead of the aorta [ 16 ]. However, sampling the tiny arteries that feed bone marrow is impractical due to their being difficult to identify, highly variable, and of noisy signal intensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation